The 1st International Electronic Conference on Plant Science 2020
DOI: 10.3390/iecps2020-08724
|View full text |Cite
|
Sign up to set email alerts
|

Nutrient Interactions in the Natural Fortification of Tomato with Mg: An Analytical Perspective

Abstract: In the human body, about 53% of Mg is involved in the development and maintenance of bone and other calcified tissues, although it also has a physiological role in protein synthesis, muscle and nerve functions, blood glucose control and blood pressure regulation. Nevertheless, Mg deficiency triggers electrolyte disturbance that can result in multiple symptoms, namely, tremors, poor coordination, muscle spasms, loss of appetite, personality changes, and nystagmus. Complications may include seizures or cardiac a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
1
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…Tomatoes biofortified with MgSO4 showed a higher content of Mg (except in the 6% MgSO4 treatment) regarding control, indicating that biofortification occurred and had a better index with the lower concentration applied (4% MgSO4). Previously, another study carried out with the same variety also showed with 4% MgSO4 treatment the highest Mg content [15]. Nevertheless, the higher content of Mg in the 4% MgSO4 treatment showed a lower Fe content, presenting a tendency of antagonism in the biofortified tomatoes considering that as the Mg content increased, the Fe content decreased.…”
Section: Discussionmentioning
confidence: 73%
“…Tomatoes biofortified with MgSO4 showed a higher content of Mg (except in the 6% MgSO4 treatment) regarding control, indicating that biofortification occurred and had a better index with the lower concentration applied (4% MgSO4). Previously, another study carried out with the same variety also showed with 4% MgSO4 treatment the highest Mg content [15]. Nevertheless, the higher content of Mg in the 4% MgSO4 treatment showed a lower Fe content, presenting a tendency of antagonism in the biofortified tomatoes considering that as the Mg content increased, the Fe content decreased.…”
Section: Discussionmentioning
confidence: 73%
“…In the middle of the biofortification workflow (after the 3rd foliar spraying with Fe and Zn), the color of the tomatoes (control and sprayed with Fe and Zn-T1 and T2) was assessed (Figure 2). All the treatments of the three varieties showed a highest value at 650 nm, corresponding to the red color [18] and, thus, being an indicator of high lycopene content [19]. Therefore, the use of this technology allowed an objective definition of the maturation state of the fruits, since red is an indication of 10 times more lycopene content than yellow [20].…”
Section: Discussionmentioning
confidence: 95%
“…Colorimetric parameters were determined in fresh tomatoes per treatment with a scanning spectrophotometric colorimeter, according to Reference [18]. Measurements were carried out in quadruplicate.…”
Section: Colorimetric Parametersmentioning
confidence: 99%